Serum procacitonin as a diagnostic marker of bacterial infection in febrile children - K., Brindha; Manickam, Kumar; Ulagaratchagan, Santhakumari; Kumar, Mohan; Sampath, Sowmya; Sivathanu, Shobhana (International Journal of Contemporary Pediatrics, 2017)
Background: Early and accurate diagnosis of bacterial infections in children is important as the outcome is dependent on it. Various tests and biomarkers have been used for this among which serum procalcitonin shows a lot of promise. The aim of the study was to determine the role of serum procalcitonin as a diagnostic marker of bacterial infection in febrile children. Methods: All acutely febrile children between 6 months to 12 years of age were enrolled in this prospective study. The efficacy of procalcitonin (PCT), highly sensitive C-reactive protein (hs CRP) and absolute neutrophil count (ANC) in diagnosing bacterial infections was compared. Results: Among the three parameters, PCT has the highest area under the receiver operating characteristic curve (AUC) (O.755), followed by CRP (AUC 0.717) and ANC (AUC 0.628). Conclusions: In summary, our study showed that PCT performs better than hs CRP and ANC in detecting bacterial infection in febrile children.